2014
DOI: 10.4172/2329-6917.1000129
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluations of Hematological Malignancies Compared with Solid Tumors

Abstract: Introduction: Cancer care costs escalated with the introduction of novel therapies. Therefore, cancer-related Cost Utility Analyses (CUAs) are used to guide policy makers. Since numerous methods (criteria) exist to evaluate CUAs, we compared these criteria between CUAs of solid tumors and those of hematological malignancies. Methods:A systemic MEDLINE search of English-language publications between 2001 and 2012 was performed. Strict inclusion criteria were limited to CUAs examining one single intervention and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Dr Wetzler's work suggested that a drug such as decitabine may be arguably considered for elderly newly diagnosed AML patients given the economic pressures in the US health system; however, this is not a criterion for drug approval [3]. However, as certain cancers are rare; applying economic model to clinical outcome to demonstrate which drug is more cost effective in an era of increasing economic pressures is reasonable [4]. Especially those cancer patients who express fear of bankruptcy in light of the costly cancer care [5].…”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…Dr Wetzler's work suggested that a drug such as decitabine may be arguably considered for elderly newly diagnosed AML patients given the economic pressures in the US health system; however, this is not a criterion for drug approval [3]. However, as certain cancers are rare; applying economic model to clinical outcome to demonstrate which drug is more cost effective in an era of increasing economic pressures is reasonable [4]. Especially those cancer patients who express fear of bankruptcy in light of the costly cancer care [5].…”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…However, in the paucity of patients in certain rare tumors researchers may consider speculative models to wisely pilot our allocation of our scarcely earned dollar on a specific treatment. The advantage of such models in rare tumors may ensue from considering a significant large patient population in each arm of the analysis while adopting real-time survival probabilities and cost data [4].…”
Section: Editorialmentioning
confidence: 99%